In the beginning an introduction to Archaeology - Fagan, Brian M. (Harper Collins, 1991)
Contents of this book include: Background to archaeology; Ashort history of archaeology; Data and context; Recovering archaeological data; Reconstructing past lifeways; Interpreting culture change in the past; Cultural resourse management.